Cross Sectional Study of Burn - Experience in 158 Cases (Delta Medical College Journal, 2018)
Background: Burns are a global public health problem.Objectives: To find out the status of burn victims along with the causes and consequences of fatal burn injuries.Material and method: The data is collected from the autopsy reports of Dhaka Medical College in 2012. The purpose of this study was to record and evaluate the causes and magnitude of the fatal burn injuries.Results: In 2012, among total 2527 deaths reported at Dhaka Medical College, 158 (6.25%) cases were due to burn. The victims within 21 to 40 years were more vulnerable in comparison to other age groups. Female were more vulnerable than male (55.69% vs. 44.31%). Accidental burn was the commonest cause (55%).Conclusion: Thermal burns and related injuries are major cause of death and disability all over the world as well as Bangladesh. Detail study regarding flame burn is required to be carried out in this country.Delta Med Col J. Jan 2018 6(2): 82-85